Mendorong Kesiapan Berkarir Pemuda Pathuk, Patutrejo di Era Revolusi Industri 4.0 - Yune Andryani Pinem; Esti Nur Wakhidah; Walid Jumlad (Randang Tana - Jurnal Pengabdian Masyarakat, 2022)
Maximizing youth as a region asset must be accompanied by comprehensive training. The focus of the training was Pathuk youth in the Karang Taruna Organization. The purpose of the training is to bring out the best potential of Pathuk youth and to prepare them with entrepreneurship skills in the forth industrial revolution era. The training begins with the participant’s self-mapping based on their strengths and weaknesses. Furthermore, online marketing training is carried out by adjusting the natural and human potential of this region. The introduction and use of English-based online shopping features are the skills to train as a provision for aiming at the digital market. Through lecturing, discussing, and question-and-answer methods, the entire training has been proven to bring out the potential of natural and human resources in the Pathuk area which has not been exposed earlier. Self-introspection of participants, and models of online marketing, both in Indonesian and English, were the outcomes generated from this training. The paradigm shift was obtained from the responses of participants who completely participated in the training